A língua brasileira de sinais na ilha de São Luís: um estudo sociolinguístico de variação lexical - AZEVEDO, Renan Pires (2025)
Understanding that sign languages undergo processes of variation and linguistic change, just like other natural languages, this study analyzes variation in the signing of lexical items within the semantic fields of animals, food, social interaction, colors, the human body, fruits, professions, and clothing and accessories by deaf individuals residing on the island of São Luís, in Maranhão. This research takes into account the social characteristics of the participants, aiming to verify whether variation exists in the signing of the aforementioned semantic fields, allowing for the observation of whether different ways of signing the same referent constitute a phenomenon of lexical variation—indeed, as variants of the same variable—or whether, on the contrary, they should be understood as a sign or classifier. The data were collected through interviews with deaf individuals who attend the Center for Education and Support for Deaf Individuals Maria da Glória Costa Arcangeli – CAS, in order to discuss how this community aligns with Eckert's (2000) concept of communities of practice, as they share repertoires of practices, including linguistic ones. As proposed in this study, they would constitute a deaf community of practice. The theoretical-methodological framework is based on Variationist Sociolinguistics (Labov, 2008 [1972]) and studies on sign language (Stokoe, 1960; Quadros & Karnopp, 2004). This study found that men were more innovative, while women were more conservative. For items that have dictionary records, higher education informants mostly exhibited greater recurrence in the use of these signs. Informants with a high school education and those in age group 2 used more iconic forms in their production of the items. This study contributes theoretically by bringing to the forefront discussions on variants of the same variable in Brazilian Sign Language (Libras) and criteria for determining whether a variation is lexical, a variant of the same variable, or a classifier. Additionally, it contributes to the concept of community in sociolinguistic studies of signed languages. Methodologically, it proposes a framework for sociolinguistic description of data from sign languages in deaf communities.